When they met again - Gould, Leslie, 1962- (Gould, Leslie, 1962- Letters from Lancaster County, 2026)
"It's love at first sight for Adam Slaybaugh, but Joanna Grebel insists they be "just friends." When Adam returns to Lancaster County years later, he finds Joanna suffering from a broken heart. Misunderstandings and matchmaking schemes begin a tender journey of healing and romance-but is Adam's love enough to finally win Joanna over?" -- Provided by publisher.